Mother Hummingbird Based on a Play by Henry Bataille - Coppola, Antonio; Bataille, Henry (Cinema of Discovery: Julien Duvivier in the 1920s, 2021)
A neglected Baroness falls in love with her oldest son's military officer friend, their adulterous romance leading the two to flee to Algeria. [letterboxd.com]